Antiviral activity of leaf-bud gum-resin of Tarenna asiatica (Bangladesh Journal of Pharmacology, 2014)
The leaf-bud exudate of Tarenna asiatica (Rubiaceae: Ixoroideae, Pavetteae) is investigated for its biological activity. The crude benzene extract and corymbosin (pure compound isolated) were screened for antiviral activity by using ELISA and PCR methods against animal (blue tongue and chikungunya) and plant (papaya ring spot, sesbania mosaic and common bean mosaic) viruses. Both corymbosin and benzene extract showed significant antiviral activity though corymbosin was found relatively more potent against the animal and plant viruses tested. This is the first report of antiviral activity for the gum-resin of T. asiatica, so also for the compound corymbosin, against the plant viruses.